Laser Induced Fluorescence of N2+(X, v") Resulting From the Thermal Energy Dissociative Charge Transfer Reaction He++N2O→N2++O+He. Issue 1 (1989) - Lemaire, j.; Marx, R.; Savary, F. Morlet
Abstract : The vibrational (and rotational) energy distribution ofN 2 + (X) ions produced in theHe + / N 2 O charge transfer reaction at thermal energy has been measured by laser induced fluorescence using an Ion Cyclotron Resonance cell to store the ions. Vibrational levels up toV " = 5 have been observed. The relaxation processes experienced by theN 2 + (X) ions before laser detection are discussed.